THE ROMANIAN IMMIGRANTS FROM ITALY IN THE CONTEXT OF THE RECENT ECONOMIC CRISIS - Simionescu, Mihaela (International Journal of Psychosocial Rehabilitation, 2020)
considering the influence of the recent economic crisis on migration process, the main aim of this paper is to identify changes in the structure of Romanian migration to Italy and the impact of various factors on their job losses at a certain time. Using statistical tests and a random-effects ordered logistic regression based on the survey data, we showed significant differences between the number of males and females and also in their age distribution. The economic crisis increased the gap between the number of males and females. The results based on the regression model indicate that the economic crisis did not have a significant impact on the job losses of Romanian migrants at a certain time. Factors like gender and professional position explain the unemployment of migrants. The results are confirmed by the expectations as foreign women have more chances to find a job in Italy as compared to men and the jobs in some sectors like services and construction are more vulnerable to unemployment.